Effects of Biogas Plant Residues and NPK Fertilizers on Growth and Nutritional Quality of Amaranth (Amaranthus tricolor L.) - Chowdhury, F. J.; Kibria, M. G.; Alamgir, M.; Islam, M. (International Journal of Bio-resource and Stress Management, 2023)
A pot experiment was conducted at crop field of the Dept. of Soil Science, University of Chittagong to study the effect of biogas plant residues (BPR) and NPK fertilizers on the growth of and nutrient uptake by Amaranth (Amaranthus tricolor L.). There were six treatments and treatments were consisted as the following: T1=Control (No BPR+No inorganic fertilizers), T2=recommended doses of NPK @ 156 kg N ha-1, 36 kg P ha-1, 80 kg K ha-1 from inorganic fertilizer, T3=BPR @ 20 t ha-1+calculated amount of inorganic NPK fertilizer, T4=BPR @ 15 t ha-1+calculated amount of inorganic NPK fertilizer, T5=BPR @ 10 t ha-1+calculated amount of inorganic NPK fertilizer, T6=BPR @ 5 t ha-1+calculated amount of inorganic NPK fertilizer. Each treatment was replicated thrice. The results showed that the minimum no. of leaves, plant height, root length and fresh and dry weight of shoot and root were found in control treatment T1. The no. of leaves and plant height were the maximum in treatment T4 in most cases. However, the highest shoot and root weight was observed in treatment T6. Compared to inorganic fertilizer alone, the application of biogas residues along with NPK fertilizers applied at reduced rates significantly increased dry weight of shoot and root of amaranth by 38–54% and 91–166% respectively. Nutrient uptake was the lowest in control, higher in the treatment of chemical fertilizer alone and the highest in the treatments of biogas plant residues in combination with chemical fertilizers except Ca uptake in shoot. The results of the present study suggest that the application of biogas residues along with reduced rate of inorganic fertilizers is a viable strategy for the sustainable production of amaranth in valley soils of Chittagong.